Heliannuol: Distribution, Biological Activities, 1H and 13C-NMR Spectral Data - Ribeiro, Carlos M. R.; de Souza, Thiago Silva Galvão; de Almeida, Karinne C.; Dutra, Karen Danielle Borba; Valverde, Alessandra Leda (Mini-Reviews in Organic Chemistry, 2020)
Heliannuols are an important class of compounds isolated from Helianthus annuus, a common sunflower, with allelopathic properties. Interestingly, two of these fourteen compounds have been isolated from a gorgonian, Pseudopterogorgia rigida. This review compiles data on the isolation and biological activity of heliannuols described in the literature and briefly reports the papers describing their syntheses. This review could stimulate research into other natural species and syntheses. Further, it describes the 1H and 13C-NMR spectral data described in the literature for the 14 heliannuols already isolated and correlates them with their respective structures. Therefore, we believe that these searchable data enable a rapid identification in routine analysis of the crude extracts of sunflowers or gorgonians.
Keywords: heliannuols